Pembentukan Konsep Pengaturan Upah di Atas Upah Minimum Yang Berkeadilan Bagi Pengusaha dan Pekerja (Jurnal Hukum Bisnis Bonum Commune, 2022)
This research aims to propose ideal pattern of wages above minimum wage which could bring justice for entrepreneurs and labors. This research used normative research which examine the existing legal norms with conceptual approach, proposing a solutive concept on the problem of the wages above the minimum wage. The results show that the recent concept of wage above minimum wage is difficult to be implemented because it is strictly based on consensus. Thus, there must be determination of minimum value of the increase made by the government. The ideal amount should be as much as the percentage of the increase of minimum wage from the recent to the coming year, or if there is no increase by the coming year, as much as 50 percents of inflation. This concept must be governed in the implementing regulation such as government regulation.